2017
DOI: 10.5588/ijtld.16.0357
|View full text |Cite
|
Sign up to set email alerts
|

Stool Xpert® MTB/RIF test for the diagnosis of childhood pulmonary tuberculosis at primary clinics in Zimbabwe

Abstract: SUMMARYOBJECTIVE: To evaluate the diagnostic performance of Xpert® MTB/RIF on stool samples from children with clinical suspicion of pulmonary tuberculosis (PTB) at primary care clinics.DESIGN: A cross-sectional diagnostic evaluation enrolling 5–16 year olds from whom one induced sputum (IS) sample was tested for microbiological TB confirmation. Results of a single stool sample tested using Xpert were compared against microbiologically confirmed TB, defined as a positive result on sputum microscopy and/or cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 23 publications
(24 reference statements)
6
30
2
Order By: Relevance
“…This is the first large study, since initial proof-of-concept ( 10 ), to evaluate the performance of a novel centrifugation-free processing method for stool specimens, to assess its use with the Xpert MTB/RIF assay on stool to diagnose TB in children. Compared to microbiological confirmation using respiratory specimens, this method demonstrated diagnostic accuracy similar to those of recently published studies in young children ( 7 , 8 , 15 ), while studies enrolling mainly older children reported higher sensitivities for stool Xpert ( 9 , 16 , 17 ). This is most likely due to the lower bacillary concentrations present in respiratory specimens and, hence, in stools of young children, who seldom present with adult-type (cavitating) TB ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 73%
“…This is the first large study, since initial proof-of-concept ( 10 ), to evaluate the performance of a novel centrifugation-free processing method for stool specimens, to assess its use with the Xpert MTB/RIF assay on stool to diagnose TB in children. Compared to microbiological confirmation using respiratory specimens, this method demonstrated diagnostic accuracy similar to those of recently published studies in young children ( 7 , 8 , 15 ), while studies enrolling mainly older children reported higher sensitivities for stool Xpert ( 9 , 16 , 17 ). This is most likely due to the lower bacillary concentrations present in respiratory specimens and, hence, in stools of young children, who seldom present with adult-type (cavitating) TB ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 73%
“…We observed the sensitivity of stool Xpert to be 88.9% as compared with GA culture, 100% with GA Xpert and 81.8% with GA Xpert. The stool Xpert sensitivity we observed was higher than that shown by Nicol et al in non-HIV children [ 6 ] and by Chipinduro et al in HIV and non-HIV children [ 13 ] possibly, due to the screening tool (modified KJ score) we used to recruit children with high likelihood of TB. However, the sensitivity of Xpert stool we observed was similar to that reported by Banada et al [ 14 ] who tested larger quantities of replicate stool samples from children with pediatric TB.…”
Section: Main Textcontrasting
confidence: 72%
“…In this study, the prevalence of pulmonary tuberculosis among children is 5.73% (22/384), which is similar to the finding in Tanzania (5.2%). 34 However, it is higher than the findings reported in Zambia (1.58%), 35 Mozambique (1.65), 36 South Africa (1.3%), 37 and lower than reports from India (15%), 38 Zimbabwe (8.7%), 39 Greenland (8.5%), 40 South Africa (13%), 41 Uganda (10%), 42 Ethiopia (13.6%), 43 Bangladesh (32.97%) 44 and Nigeria (32%). 45 The reason for variation might be due to the difference in the prevalence of tuberculosis in the general population, methods of sputum sample collection and diagnosis.…”
Section: Discussionmentioning
confidence: 63%